Pectin Induced Colony Expansion of Soil-Derived Flavobacterium Strains - Kraut-Cohen, Judith; Shapiro, Orr H.; Dror, Barak; Cytryn, Eddie (Frontiers in Microbiology, 2021)
The genus Flavobacterium is characterized by the capacity to metabolize complex organic compounds and a unique gliding motility mechanism. They are often abundant in root microbiomes of various plants, but the factors contributing to this high abundance are currently unknown. In this study, we evaluated the effect of various plant-associated poly- and mono-saccharides on colony expansion of two Flavobacterium strains. Both strains were able to grow on pectin and other polysaccharides such as microcrystalline cellulose. However, only pectin (but not pectin monomers), a major component of plant cell walls, enhanced colony expansion on solid surfaces in a dose- and substrate-dependent manner. On pectin, flavobacteria exhibited bi-phasic motility, with an initial phase of rapid expansion, followed by growth within the colonized area. Proteomic and gene expression analyses revealed significant induction of carbohydrate metabolism related proteins when flavobacteria were grown on pectin, including selected SusC/D, TonB-dependent glycan transport operons. Our results suggest an unknown linkage between specific operons encoding for glycan uptake and metabolism and flavobacterial expansion. Furthermore, within the context of flavobacterial-plant root interactions, they suggest that plant root pectin may facilitate flavobacterial expansion on root surfaces in addition to serving as an essential carbon source.